Gaya Kepemimpinan dan Motivasi Kerja Pegawai Bank Negara Indonesia (Persero) Tbk Kantor Cabang Utama Manado - Korua, Michael D; Lumolos, Johny (JURNAL ILMU ADMINISTRASI (JIA), 2012)
Abstract: The research objective was to identify and describe the leadership style and employee motivation to work at the Main Branch of BNI Manado. The research method used was qualitative research by collecting data through interviews, observation and documentation. Informant were obtained based on the consideration of researchers, those who provided an objective and accurate information in accordance with research problems. Informants were drawn from a bank employee BNI Main Branch Manado with the total of 11 consisting of five informants in the frontliner, three from the marketing and three Â from the back office. The results showed leadership style inclined toward participatory because accommodate suggestions, proposals and opinions from subordinates by using strict rules and discipline to influence subordinates, employees were required to implement the provisions of service standards for frontliner upon request or demand of management. Most of frontliners were required to meet the demands of the service standards without bargaining for the progress of BNI. Leaders received suggestions and proposals put forward subordinates because subordinates were at the forefront in receiving comments from customers. Motivation of employees currently working was like to achieve the best career, get high salaries, inadequate facilities and getting adequate pensions. It can be suggested that in improving the performance of banks in accordance with the goals, vision and mission of BNI be a participative leadership style tailored to let maintained even listening to what customers want as a customer. Leaders have to noting employees who experienced demotivation caused by too saturated with the situation and working conditions by providing a variety of tasks, and create a conducive atmosphere in the workplace. Keywords : Leadership Â Style and Employee Motivation